REVOLUTIONIZING TOURISM: UNLEASHING THE POWER OF EXPERIMENTAL DESIGN - Purnomo, Sodik Dwi; Retnowati, Diah; Zumaeroh, Zumaeroh (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Developing tourism attractions in regions is essential to boost local communities' well-being and revenue. However, these attractions face challenges from various sources, including internal and external factors like funding and development strategies. This study focused on identifying financing sources and effective strategies for developing tourism attractions in the region, using Serulingmas Interactive Zoo in Banjarnegara Regency as a case study. The research methods were contingent valuation method, logistic regression, and SWOT analysis. This study's main novelty is its approach, blending the Contingent Valuation Method, Binary Logistics Regression Analysis, and SWOT Analysis to tackle the research question. It also conducted experiments with three distinct questionnaires. The research results showed that to increase revenue as a source of financing, Serulingmas Interactive Zoo could increase ticket prices by IDR 6,505.62 on weekdays and weekends. The development strategy of Serulingmas Interactive Zoo emphasized opportunities and strengths through the SO and WO strategies and minimized weaknesses and threats through the ST and WT strategies. This research implication suggests boosting funding for Serulingmas Interactive Zoo by raising entrance fees and using strategic approaches (SO, WO, ST, and WT) to enhance its performance. It also hints at broader implications for various domains and highlights areas for future research and unanswered questions.